Dual‐Site Functionalization on Supported Metal Monolayer Electrocatalysts for Selective CO2 Reduction (Adv. Energy Mater. 3/2023). Issue 3 (20th January 2023) - Zhao, Zhonglong; Lu, Gang
Abstract : CO2 Electroreduction In article number 2203138, Zhonglong Zhao and Gang Lu predict that noble metal monolayers supported by transition metal carbides (TMCs) and nitrides (TMNs) could be selective catalysts for the carbon dioxide reduction reaction with suppressed hydrogen evolution reaction. Dual‐site functionalization induced by antibonding interactions between hydrogen and the TMC/TMN substrates is identified, which can circumvent energy scaling relations and enable active, selective, and robust CO2 electroreduction.